Menguji Pengaruh Gaya Hidup, Motivasi Dan Persepsi Harga Terhadap Keputusan Pembelian Iphone: Studi Pada Mahasiswa UNISKA MAB Banjarmasin - Abdul Razak; Erni Alfisah; Purboyo Purboyo (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The purpose of this research study was to examine the effect of lifestyle variables (X1), motivational variables (X2) and price perception variables (X3) on the decision to buy an iPhone among students at the Islamic University of Kalimantan (UNISKA). research method with a quantitative approach, the population considered in the study consisted of Management Study Program students totaling 90 respondents. Data analysis techniques using descriptive statistics, instrumental testing, classical hypothesis testing, multiple linear regression analysis, and hypothesis testing. This test was carried out using the statistical software SPSS version 26. The results of this study partially indicate that lifestyle variables (X1) do not have a significant influence on purchasing decision variables. Motivation variable (X2) has a significant influence on purchasing decisions. Price perception variable (X3) has a significant influence on purchasing decisions. Based on simultaneous testing of lifestyle variables (X1), motivation (X2) and price perceptions (X3) jointly have a significant effect on the iPhone purchasing decision variable for UNISKA Banjarmasin students.